2010
DOI: 10.1299/jpes.4.348
|View full text |Cite
|
Sign up to set email alerts
|

Anode Reaction in Pressurized Solid Oxide Fuel Cells

Abstract: Pressurized solid oxide fuel cells (SOFCs) using a gas turbine for the bottoming cycle convert energy very efficiently. The performance of a tubular SOFC made by a plasma spray coating method was measured at levels of pressure between 0.1 and 0.59 MPa. The cell voltage increased with the operating pressure. Moreover, it was determined that polarization decreased under pressurization, using the current interruption. Anode performance was also measured with a reference electrode. The estimated concentration over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…For instance, Eguchi and his co-workers (4) measured a symmetrical Ni/YSZ anode half-cell at elevated pressures (p). They obtained an increase of the anodic concentration overvoltage with increasing p. But Hashimoto et al (13) who also measured the anode reaction in a tubular PSOFC found that the concentration overvoltage did not depend on the operating pressure, and the voltage rise over the Nernst voltage due to pressurization was attributed to the decrease in the activation overvoltage. Furthermore, in a numerical study (6), Henke et al reported a decrease of the anodic concentration polarization with increasing p. Hence, one of the objectives of this paper is to investigate the aforesaid discrepancy concerning the effect of pressurization on the anodic concentration overvoltage of PSOFC.…”
Section: Introductionmentioning
confidence: 96%
“…For instance, Eguchi and his co-workers (4) measured a symmetrical Ni/YSZ anode half-cell at elevated pressures (p). They obtained an increase of the anodic concentration overvoltage with increasing p. But Hashimoto et al (13) who also measured the anode reaction in a tubular PSOFC found that the concentration overvoltage did not depend on the operating pressure, and the voltage rise over the Nernst voltage due to pressurization was attributed to the decrease in the activation overvoltage. Furthermore, in a numerical study (6), Henke et al reported a decrease of the anodic concentration polarization with increasing p. Hence, one of the objectives of this paper is to investigate the aforesaid discrepancy concerning the effect of pressurization on the anodic concentration overvoltage of PSOFC.…”
Section: Introductionmentioning
confidence: 96%
“…For instance, Eguchi and his coworkers (6) studied experimentally a symmetrical anode half-cell at elevated pressures and they found that the concentration polarization increased with increasing p via the measurement of the anode concentration overvoltage. But Hashimoto et al (7) who investigated experimentally the anode reaction in a tubular PSOFC reported that the ohmic loss and concentration overvoltage do not depend on the operating pressure. They further suggested that the voltage rise over the Nernst voltage was due to the decrease in the activation overvoltage.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Eguchi and his co-workers 6 studied experimentally a symmetrical Ni/YSZ anode half-cell at elevated pressures and reported that the concentration polarization increased with increasing p via the measurement of the anode concentration overvoltage. But Hashimoto et al 7 who also investigated experimentally the anode reaction in a tubular PSOFC suggested that the concentration overvoltage did not depend on the operating pressure, and the voltage rise over the Nernst voltage due to pressurization was attributed to the decrease in the activation overvoltage. Furthermore, Henke et al 8 studied the problem numerically and they predicted a decrease of the concentration polarization with increasing p, just opposite to the experimental result.…”
mentioning
confidence: 99%